2021
DOI: 10.3390/su13031104
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Spatial Heterogeneity and Correlation Network of Green Innovation Efficiency in China

Abstract: With environmental problems becoming increasingly serious worldwide, scholars’ research views on innovation have begun to pay more attention to the technological value from an ecological perspective, instead of simply analyzing the importance of technological innovation from the perspective of economic value. Currently, improving green innovation efficiency (GIE) has been considered as a critical path to realizing economic transformation and green development. Based on the global Super-Epsilon-based measure (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…As the economy of China develops, environmental challenges facing the country are on the rise, depicting the idea of substituting economic growth for a green [1] and sustainable environment [78]. A green economy utilizes less water [13] and minimizes pollution through the discharge of wastewater and other forms of pollutants [29]. The discharge of excessive industrial wastewater is prominent in Jiayuguan and Pingliang cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the economy of China develops, environmental challenges facing the country are on the rise, depicting the idea of substituting economic growth for a green [1] and sustainable environment [78]. A green economy utilizes less water [13] and minimizes pollution through the discharge of wastewater and other forms of pollutants [29]. The discharge of excessive industrial wastewater is prominent in Jiayuguan and Pingliang cities.…”
Section: Discussionmentioning
confidence: 99%
“…Based on panel data from 28 provinces in China and using research and development expenditure input as a key indicator, [28] found differences in green development efficiency (GDE) of the provinces with Beijing (1.273) and Shanxi (0.219) ranking the highest and lowest, respectively. Similarly, [29] reported that in spatial terms, China's green innovation efficiency is unbalanced across the 30 provinces considered in their study from 2009-2017. Green innovation efficiency is higher in the eastern region than the national level, while the other regions are central > western > northeastern.…”
Section: Introductionmentioning
confidence: 97%
“…(1) Network density: Network density is used to evaluate the extent of the inter-industry correlation in the network [ 38 ]. The greater the number of association relationships in the network, the greater the network density [ 39 ]. The value of density ranges from 0 to 1, and the closer it is to 1, the greater the network density is.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, using the method of the Dagum Gini coefficient and its subgroup decomposition, kernel density estimation, and the spatial Markov chain, Yao et al (2022) discussed the convergence characteristics and dynamic evolution rule of industrial green technology innovation efficiency in 110 cities of the Yangtze River Economic Belt from 2006 to 2020 (Yao et al, 2022). Utilizing the combination of the global Super-Epsilon-based measure (EBM) model, vector autoregression model, block model, and Moran index, Wang and Zhang (2021) conducted an empirical study on the spatial-temporal features of the green innovation efficiency of China's 30 provinces and analyzed its spatial heterogeneity and spatial correlation network characteristics (Wang and Zhang, 2021). Moreover, some scholars have conducted studies on the spatial differences in green innovation efficiency using different scales.…”
Section: Literature Reviewmentioning
confidence: 99%